Benefits of spark-ignition engine fuel-saving technologies under transient part load operations - W. Salim, W.S.I.; Mahdi, A.A.M.; Ismail, M.I.; Abas, M.A.; Martinez-Botas, R.F.; Rajoo, S. (Universiti Malaysia Pahang, 2017)
This paper presents a simulation-based study to evaluate three potential benefits of fuel-saving technologies implemented in spark-ignition (SI) engines for a passenger car over actual urban driving cycles. These technologies include cylinder deactivation (CDA), stop-start system, and engine downsizing (≈20% degree of downsizing). The aim of the work is to evaluate individual benefits of each system in terms of fuel consumption. GT-Power engine simulation tool is utilised to model engines which employ each of the mentioned technologies; each of the engines has identical full-load torque characteristics. Each engine model is instructed to run over a transient, part-load, torque driven operations based on actual road test measurements, and the cycle-averaged fuel consumption was evaluated. From the analysis, the contribution of each technology in terms of fuel economy can be assessed based on an actual part-load transient operation, which can be beneficial to developers to optimise the operation of SI engines. The results revealed stop-start system to be the most promising technology for the driving cycle at hand with 27.5% fuel consumption improvement over the baseline engine. CDA engine allows for 12.6% fuel economy improvement. On the other hand, the downsized turbocharged engine has caused increasing cycle fuel consumption by 7.5%. These findings are expected to be valid for typical urban driving cycles as far as they conform to the operating load residency points over the transient torque profile.